Os entrelugares educação infantil-ensino fundamental : o que podem os currículos tecidos com os cotidianos das escolas? - Silva, Tamili Mardegan da (2018)
This study is a dive (ALVES, 2001) in the daily life of an EMEIEF (Municipal School of Early Childhood Education and Elementary School) crossed by children's movements in the composition of curricula. In the midst of the macro-policies of the curriculum focused on these stages, there are daily microactions (CERTEA, 2014) that help this research to support the idea that a curriculum written by a minor literature (DELEUZE; GUATTARI, 2017), produced by childhood, is an intensifier of learning and needs to occupy space in the educational discussions. In minor education (GALLO, 2016), which infiltrates sovereign education, we find the true power of the curriculum carried out (FERRAÇO, 2011) that goes beyond what is officially thought to happen in school. With methodological inspirations coming from the researches with the daily ones (FERRAÇO, 2003), this writing treats of the curricula woven in the interlacings (BHABHA, 2013) infantile education-fundamental education, problematizing the processes that move this educational foundation, as well as the possible compositions in these meetings within (Alves, 2010a) of school space-times. What is tense here is an education affected by the becoming-child (DELEUZE; GUATTARI, 2012b) who acts as a war machine in defense of childhood and militating against macro-pressures, since it argues that there is no age demarcated for educational processes, according to the determinism of the National Curricular Guidelines (DCNs) and, especially, of the National Curricular Common Base (BNCC). The prescriptive curricular policies show the predominance of literacy in both primary and secondary education (EI-EF), even though in the first stage it appears more veiled and in the initial years it presents itself explicitly, categorizing the stages as opposites, but who share the need for literacy to promote the desired linearity for a secure transition between them. Questions, therefore, that literacy goes far beyond this standardized path, as well as the transgressions between EI-EF, which surpass any logic of binarisms. Therefore, this research concludes that macropolitics impositions, such as timing, aging, grading and behaving (CERTEAU 2014) do not withold the crosswise power of curriculums that break what is traditionally instituted.